Neuromodulation influences T lymphocyte calcium signaling and alpha synuclein clearance: implications for Parkinson’s disease - Ross, Alysia; Prowse, Natalie; Zhang, Hui; Hayley, Shawn; Sun, Hongyu (Frontiers in Cellular Neuroscience, 2025)
Along with the death of midbrain dopamine neurons, pathological accumulation of aggregated alpha synuclein (α-syn), often in the form of Lewy bodies, forms the hallmark pathological features of Parkinson’s disease (PD). Evidence of a neuroinflammatory response is a common secondary feature present in virtually all PD brains and is characterized by the presence of reactive microglial cells and signs of peripheral immune cell infiltration. Recent research has even suggested that PD might actually have an autoimmune component, as some PD patients express T cells that recognize epitopes specific to α-syn. Although neuromodulation is one of the leading treatment options for PD motor symptoms through regulating neuronal excitability, its impact on underlying α-syn and neuroimmune pathology remains poorly understood. While immune cells, such as T lymphocytes, have historically been thought to be non-excitable cells, their expression of L-type Ca2+ channels may suggest otherwise. In fact, these channels are thought to have an important role in CD4 + and CD8 + T cell proliferation, survival and cytokine release. Since emerging evidence suggests α-syn-specific T cell responses may be important in PD, we posit that neuromodulatory treatments may be useful for “reprograming” T cell functioning. In this review, we will summarize the role of α-syn specific T cell responses in PD pathology and consider the role of L-type Ca2+ channels on CD4 + and CD8 + T cells responses in the disease. We will then discuss the effect of neuromodulatory treatments on T cell-mediated immune responses and α-syn structure in an attempt to explain why treatments involving electrical stimulation are beneficial for PD patients.